Botfly infections impair the aerobic performance and survival of montane populations of deer mice, Peromyscus maniculatus rufinus. (21st January 2019) - Wilde, Luke R.; Wolf, Cole J.; Porter, Stephanie M.; Stager, Maria; Cheviron, Zachary A.; Senner, Nathan R.
Abstract: Elevations >2, 000 m represent consistently harsh environments for small endotherms because of abiotic stressors such as cold temperatures and hypoxia. These environmental stressors may limit the ability of populations living at these elevations to respond to biotic selection pressures—such as parasites or pathogens—that in other environmental contexts would impose only minimal energetic‐ and fitness‐related costs. We studied deer mice ( Peromyscus maniculatus rufinus ) living along two elevational transects (2, 300–4, 400 m) in the Colorado Rockies and found that infection prevalence by botfly larvae ( Cuterebridae ) declined at higher elevations. We found no evidence of infections at elevations >2, 400 m, but that 33.6% of all deer mice, and 52.2% of adults, were infected at elevations <2, 400 m. Botfly infections were associated with reductions in haematocrit levels of 23%, haemoglobin concentrations of 27% and cold‐induced VO2max measures of 19% compared to uninfected individuals. In turn, these reductions in aerobic performance appeared to influence fitness, as infected individuals exhibited 19‐34% lower daily survival rates. In contrast to studies at lower elevations, we found evidence indicating that botfly infections influence the aerobic capabilities and fitness of deer mice living at elevations between 2, 000 and 2, 400 m. Our results therefore suggest that the interaction between botflies and small rodents is likely highly context‐dependent and that, more generally, high‐elevation populations may be susceptible to additional biotic selection pressures. Aplain language summary is available for this article. Abstract : Plain Language Summary